Determination of the Connection Between the Asthma Patients and Mycobiota in the Environment They Live in - KORKMAZ, ARAS FAHRETTİN; Çolakoğlu, Günay Tülay; Karaltı, İskender (Selçuk Üniversitesi Mantarcılık Uygulama ve Araştırma Merkezi Müdürlüğü, 2023)
In the 12-month period between February 2014 and January 2015, this study was carried out in the homes of 55 asthma patients living in 14 different regions of Istanbul (Ataşehir, Bulgurlu, Fikirtepe, Hasanpaşa, İçerenköy, Moda, Göztepe, Çekmeköy, Ümraniye, Altayçeşme Neighborhood, Esenkent Neighborhood, Feyzullah Neighborhood, Gülsuyu Neighborhood, Yalı Neighborhood). Air ideal (Biomerieux, France) air vacuuming device was used to determine the fungal flora in the domestic ambient air of the relevant patients. In this context, in order to prevent bacterial growth, Streptomycin antibiotic was added and Rose Bengali potato dextrose agar was placed in the slot of the device and the air filter of the device was installed. The device, which was placed at a height of 75-85 cm from the ground, was operated for 3-5 minutes and 200 liters of domestic ambient air was vacuumed. A total of 1071 microfungi colonies isolated in the study were found to belong to a total of 10 genuses and 23 species. The obtained genera are Alternaria (Arıküfü), Aspergillus (Asper), Aureobasidium (Karamaya), Chaetomium (Günoku), Cladosporium (Havaküfü), Fusarium (Solduran), Mucor (Ekmekküfü), Paecilomyces (Günküfü), Penicillium (Penisilyum) and Rhizopus (Karaküf). Among them, the most isolated genera were Aspergillus, Penicillium, Cladosporium, Alternaria and Fusarium. The most isolated species in this study were Aspergillus niger (Kara asper), Fusarium poae (Buğday solduran), Alternaria alternata (Astımküfü), Cladosporium cladosporioides (Karakökküfü), Penicillium brevicompactum (Sağlam penisilyum), Cladosporium macrocarpum (İrikurutan), Cladosporium sphaerospermum (Güllekurutan) and Penicillium glabrum (Bol penisilyum). In the 12-month period, the lowest microfungi concentration was observed in January and the highest microfungi concentration was observed in May. During the study, the temperature of the sample areas were measured with a thermometer and the humidity rates were measured with a hygrometer. In this study, the types of allergen microfungus that cause the onset of asthma disease or the progression of the degree of disease are stated. These were determined as Alternaria alternariae (Fıstık küfü), Alternaria alternata, Aspergillus fumigatus (Kıran asper), Aspergillus niger, Aureobasidium pullulans (Karamaya), Chaetomium globosum (Top günoku), Cladosporium cladosporioides, Cladosporium herbarum (Yaygınkurutan), Cladosporium sphaerospermum, Penicillium chrysogenum (Penisilyum), Penicillium glabrum.
Keywords: İstanbul; Asthma; Indoor Air; Microfungi